1997
DOI: 10.1136/adc.76.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cataracts in newly diagnosed diabetes

Abstract: The morphologically distinct diabetic or 'metabolic' cataract is rare in newly diagnosed insulin dependent diabetes. The cases described are of five adolescents (three girls, two boys) with newly diagnosed insulin dependent diabetes who developed metabolic cataracts close to the time of diagnosis (0-16 months). They all had a prolonged duration of symptoms before diagnosis (4-24 months) and high glycated haemoglobin levels at diagnosis (15-21%). The pathogenesis of diabetic cataract is not well understood in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
(16 reference statements)
2
43
0
Order By: Relevance
“…1 In all, 25% of patients have cerebrospinal fluid displacement into the spinal cord canal, causing syringomyelia. 1,2 Familial clustering of CMI with and without syringomyelia has been documented in American scientific literature but this case of siblings appears to be the first instance reported in the UK.…”
Section: Commentsmentioning
confidence: 83%
See 1 more Smart Citation
“…1 In all, 25% of patients have cerebrospinal fluid displacement into the spinal cord canal, causing syringomyelia. 1,2 Familial clustering of CMI with and without syringomyelia has been documented in American scientific literature but this case of siblings appears to be the first instance reported in the UK.…”
Section: Commentsmentioning
confidence: 83%
“…1,2 It can affect visual acuity from slight visual impairment to complete blindness. 1 We report a case of acute bilateral irreversible metabolic cataract in a patient with recently diagnosed Type 1 diabetes mellitus.…”
mentioning
confidence: 99%
“…Despite a reported higher incidence of Type-1 diabetes in male patients in most studies, most series have found a female preponderance for diabetic cataract, the reason for which is not clear [5]. In the cohort of Dutta et al [2], three of five patients with Type I diabetes who developed cataracts close to the diagnosis of diabetes were female. All had a prolonged duration of symptoms and high HbA1c .…”
Section: Discussionmentioning
confidence: 91%
“…Cataracts occur earlier in life and progress more rapidly in the presence of diabetes. Diabetic or metabolic cataracts are characterized by diffuse posterior and /or anterior, subcapsular or cortical 'snowflake' opacities [2].This is followed by appearance of more diffuse cloudiness and opacification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation